Outcomes After Liver Transplantation of Patients With Indo-Asian Ethnicity. Issue 4 (April 2015) - Rocha, Chiara; Perera, M. Thamara; Roberts, Keith; Bonney, Glenn; Gunson, Bridget; Nightingale, Peter; Bramhall, Simon R.; Isaac, John; Muiesan, Paolo; Mirza, Darius F.
<x xml:space="preserve">Abstract</x> Background The impact of ethnicity on outcomes after orthotopic liver transplantation (OLT) is unclear. The British Indo-Asian population has a high incidence of liver disease but its contribution to the national deceased donor pool is small. We evaluated access to and outcomes of OLT in Indo-Asians. Methods We compared 182 Indo-Asians with white patients undergoing OLT. Matching criteria were transplantation year, liver disease, age, sex. Donor and recipient characteristics, postoperative outcomes, including patient and graft survival, OLT era (early, 1987–2001; late, 2002–2011) were compared. Survival was also analyzed by underlying disease—acute liver failure (ALF) and chronic liver failure. Results Indo-Asians had higher diabetes incidence. There were no differences in waiting time for transplantation, despite smaller body size and more uncommon blood groups (B, AB) among Indo-Asians. In the early era, patient survival for Indo-Asians with ALF was worse when compared to whites. In the late era, graft and patient survival at 1, 2, and 5 years were similar between groups. Conclusion This study demonstrates that Indo-Asian patients have equal access to OLT and comparable outcomes to whites in the United Kingdom. Survival has improved among Indo-Asian patients; this may be attributable to careful patient selection in case of ALF, though improvement of patient management may have contributed.